2021
DOI: 10.3390/ani11061667
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Curcumin Promotes Gilthead Seabream Larvae Digestive Capacity and Modulates Oxidative Status

Abstract: The larval stage is highly prone to stress due to the ontogenetic and metabolic alterations occurring in fish. Curcumin inclusion in diets has been shown to improve growth by modulating oxidative status, immune response, and/or feed digestibility in several fish species. The aim of the present work was to assess if dietary curcumin could promote marine fish larvae digestive maturation and improve robustness. Gilthead seabream larvae were fed a diet supplemented with curcumin at dose of 0 (CTRL), 1.5 (LOW), or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
(101 reference statements)
1
6
0
Order By: Relevance
“…In fact, lipid peroxidation was significantly increased in fish fed CTRL-D and BG-D while curcumin was able to improve the intestinal response to lipid peroxidation induced by the DSS chemical and tended to increase the sod and gpx transcripts. Curcumin has a strong ability to stimulate antioxidant enzyme activities and to inhibit lipid peroxidation [ 40 , 44 , 45 , 47 , 50 , 51 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ], reducing the levels of ROS and NOS, responsible for the breakdown of intestinal tight junctions, tissue injury, and necrosis [ 71 ]. An increase in the relative mRNA expression of sod , cat , gpx , gr , and gst after curcumin supplementation was found in previous studies [ 44 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, lipid peroxidation was significantly increased in fish fed CTRL-D and BG-D while curcumin was able to improve the intestinal response to lipid peroxidation induced by the DSS chemical and tended to increase the sod and gpx transcripts. Curcumin has a strong ability to stimulate antioxidant enzyme activities and to inhibit lipid peroxidation [ 40 , 44 , 45 , 47 , 50 , 51 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ], reducing the levels of ROS and NOS, responsible for the breakdown of intestinal tight junctions, tissue injury, and necrosis [ 71 ]. An increase in the relative mRNA expression of sod , cat , gpx , gr , and gst after curcumin supplementation was found in previous studies [ 44 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…A holistic view is documented between the antioxidant property and sh immunity. Antioxidative enzymes, such as SOD, CAT, and GPx protect the cellular components from oxidative stress through induce the reduction of ROS into less reactive approach (Xavier et al, 2021). The product marker of lipid peroxidation, MDA indicates the oxidative damages to the lipids.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, this developmental stage in fish is also associated with oxidative stress [115]. Xavier et al [116,117] suggested that the inclusion of curcumin in the diet of gilthead seabream postlarvae could improve their health status, enhance robustness, and increase their total antioxidant capacity and digestive capacity, while reducing protein oxidative damage and oxidative stress throughout ontogeny. ↑SOD, ↑CAT, ↑GPx, ↓MDA.…”
Section: Oxidative Stress Management In Aquatic Animalsmentioning
confidence: 99%